2020
DOI: 10.3390/ijerph17228363
|View full text |Cite
|
Sign up to set email alerts
|

Look Alike, Sound Alike: Phenocopies in Steroid-Resistant Nephrotic Syndrome

Abstract: Steroid-resistant nephrotic syndrome (SRNS) is a clinical picture defined by the lack of response to standard steroid treatment, frequently progressing toward end-stage kidney disease. The genetic basis of SRNS has been thoroughly explored since the end of the 1990s and especially with the advent of next-generation sequencing. Genetic forms represent about 30% of cases of SRNS. However, recent evidence supports the hypothesis that “phenocopies” could account for a non-negligible fraction of SRNS patients who a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 94 publications
1
9
0
Order By: Relevance
“…More than 50% patients with Dent disease will present with nephrotic-range proteinuria, which is the important reason for misdiagnosis as SRNS. One mutation in the CLCN5 gene (c.2000delC) was reported in a family of SRNS by the PodoNet cohort ( 34 ), and our case illustrated similar phenotypic traits at all ( 35 ). To our knowledge, 3 different mechanisms might explain patients with phenocopies: one for misdiagnosis: clinical or genetic misdiagnosis; the second for concomitant of two different diseases; the third one is the real phenocopy as causality was not established between certain phenotypes and genotypes.…”
Section: Discussionsupporting
confidence: 68%
“…More than 50% patients with Dent disease will present with nephrotic-range proteinuria, which is the important reason for misdiagnosis as SRNS. One mutation in the CLCN5 gene (c.2000delC) was reported in a family of SRNS by the PodoNet cohort ( 34 ), and our case illustrated similar phenotypic traits at all ( 35 ). To our knowledge, 3 different mechanisms might explain patients with phenocopies: one for misdiagnosis: clinical or genetic misdiagnosis; the second for concomitant of two different diseases; the third one is the real phenocopy as causality was not established between certain phenotypes and genotypes.…”
Section: Discussionsupporting
confidence: 68%
“…8 Reverse phenotyping is an approach in which specific clinical features are interrogated in a subsequent clinical examination once a likely molecular genetic diagnosis has been established. 29 This method has been shown to detect causative genetic variants in genes that cause syndromic Mendelian diseases, including renal diseases such as pediatric-onset steroid-resistant nephrotic syndrome, 30,31 renal cystic ciliopathies, 32 and also CAKUT. 15 Another major weakness of ES is the long list of potentially deleterious variants after initial filtering.…”
Section: Introductionmentioning
confidence: 99%
“…Reverse genetics (i.e., reframing clinical diagnosis in view of genetic results) and identification of phenocopies have already proved efficacious in guiding this process in other fields of nephrology (e.g., podocytopathies and steroid-resistant nephrotic syndrome, ciliopathies, congenital anomalies of the kidney and urinary tract, etc.) [ 33 , 34 , 35 ], paving the way for a profound revision of disease ontology. Previous studies reported on disease reclassification based on reverse genetics, including in tubulopathies [ 14 , 18 , 28 , 36 ].…”
Section: Discussionmentioning
confidence: 99%